Learning Start With a Question (LSQ) Method to Student Learning Activity in Science Subject of Class VI A SD NU Metro - Mutiara Lutfi Zakia; Muh Ngali Zainal Makmun; Lutfi Fadilah (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2025)
Learning activity is one of the important elements in learning. Activity consists of physical and mental activities, namely doing and thinking as a series that cannot be separated. This study aims to determine the application of the learning start with a question method on the material of science, especially on the material of natural disasters and their impacts of class VI A SD NU Metro and to determine the increase in student learning activity by using the learning start with a question method. Based on the results of the pre-survey and interviews, problems were found, namely the lack of attention and concentration of students, the lack of enthusiasm of students in participating in learning and the lack of interaction between teachers and students , so that students find it difficult to focus on learning, and lack of motivation in learning. This has an impact on the learning activity of students which is not optimal. This study uses a descriptive qualitative method with data collection techniques using observation, interviews, and documentation. The results of an in-depth analysis related to the application of the learning start with a question method on student learning activity show that there are better changes so that it can be said that there is an increase indicated by the change where there are some students who are not yet able to understand the reading, therefore with the application of the learning start with a question method , these children begin to be able or even can conclude from the results they read.